5
$\begingroup$

How can I prove that $$\int_{0}^{\infty }\frac{\log(1+x)}{x(1+x)}dx=\sum_{n=1}^{\infty }\frac{1}{n^2}$$

$\endgroup$

closed as off-topic by Jeel Shah, Jack D'Aurizio, Ali Caglayan, user2345215, user26857 Jan 6 '15 at 0:14

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Jeel Shah, Jack D'Aurizio, Ali Caglayan, user2345215, user26857
If this question can be reworded to fit the rules in the help center, please edit the question.

14
$\begingroup$

The substitution $u = \log(1+x)$ gives

$$I = \int_0^\infty \frac{\log(1+x)}{x(x+1)} dx = \int_0^\infty \frac{udu}{e^u-1}$$

Now by using $\frac{1}{1-x} = 1+x+x^2+\ldots$ with $x=e^{-u}$ we get

$$I = \sum_{k=0}^\infty\int_0^\infty ue^{-(k+1)u}du$$

and by integration by parts it finally follows that

$$I = \sum_{k=0}^\infty\int_0^\infty \frac{1}{k+1}e^{-(k+1)u}du = \sum_{k=0}^\infty\frac{1}{(k+1)^2}$$

Your integral can be generalized to

$$I(s) = \int_0^\infty \frac{\log^{s-1}(1+x)}{x(x+1)} dx = \int_0^\infty \frac{u^{s-1}du}{e^u-1} = \zeta(s)\Gamma(s)$$

where $\zeta(s)$ is the Riemann zeta function and $\Gamma(s)$ is the gamma function.

$\endgroup$
  • $\begingroup$ I should note that switching the the order of integration and summation (as I did above) is not always justified, but it is allowed here. A justification for this can be found in this answer. $\endgroup$ – Winther Jan 5 '15 at 22:35
  • $\begingroup$ one thing: to use the Binomial expansion we need $|x|<1$, the inequality is strict, while $e^u =1$ when $x=0$. Why is this not an issue? $\endgroup$ – Alex Jan 6 '15 at 0:11
  • $\begingroup$ @Alex Because the integrand is multiplied by $u$ which cancels the divergence at $u=0$. Another approach here that avoids this issue is to split the integral into two parts $[0,\epsilon]$ plus $[\epsilon,\infty)$ and then take the limit $\epsilon\to 0$ in the end. $\endgroup$ – Winther Jan 6 '15 at 0:24
  • $\begingroup$ Thanks. I understand that $\lim_{u} \frac{u}{e^u -1} = 1$, still a bit unclear why it justifies $\frac{1}{e^u -1} = \sum_k e^{-uk}$ expansion. $\endgroup$ – Alex Jan 6 '15 at 0:29